What constitutes a useful measure of protected area effectiveness? A case study of management inputs and protected area impacts in Madagascar. Issue 10 (12th August 2019) - Eklund, Johanna; Coad, Lauren; Geldmann, Jonas; Cabeza, Mar
Abstract: Protected areas are one of the key tools for conserving biodiversity and recent studies have highlighted the positive impact they can have in avoiding habitat conversion. However, the relationship to management actions on the ground is far less studied and we currently do not know which management actions are the most crucial for success. To investigate this, we studied the effectiveness of the protected area network of Madagascar. We estimated the impact of individual protected areas in avoiding deforestation, accounting for confounding factors (elevation, slope, distance to urban centers and infrastructure, and distance to forest edge). We then investigated whether Protected Area Management Effectiveness scores, and their different facets, explained the variation observed. We found that the majority of the analyzed protected areas in Madagascar do reduce deforestation. Protected areas with higher management scores did not perform better in terms of avoiding deforestation. We discuss potential explanations for these results, and how they might influence the validity of current methods for estimating different facets of protected area effectiveness under different deforestation scenarios.